Tax Avoidance Tactics: Exploring the Interplay Between Institutional Ownership and Transfer Pricing - Az-Zahra Putri Aulia; Ferdiansyah Ritonga (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to examine and evaluate the extent of the influence of institutional ownership and transfer pricing on tax avoidance practices in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. Tax avoidance is understood as a legal strategy and is often applied by companies to reduce the tax burden by utilizing loopholes or weaknesses in the tax regulation system. This research approach is quantitative in nature by applying multiple linear regression analysis methods based on secondary data obtained from the company's annual financial statements. The sample selection was carried out using purposive sampling technique using certain criteria, which resulted in 45 companies as samples with a total of 225 observations. Measurement of tax avoidance variables is done using the Cash Effective Tax Rate (CETR) method. The research findings indicate that neither institutional ownership nor transfer pricing has a significant effect on tax avoidance, although the direction of the relationship shown is positive and requires further research.